2023
DOI: 10.3390/sports11060109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Micronutrients and Athletic Performance: A Comprehensive Scientific Systematic Review of the Literature in Sports Medicine

Hadeel Ali Ghazzawi,
Mariam Ali Hussain,
Khadija Majdy Raziq
et al.

Abstract: The aim of this systematic review is twofold: (i) to examine the effects of micronutrient intake on athletic performance and (ii) to determine the specific micronutrients, such as vitamins, minerals, and antioxidants, that offer the most significant enhancements in terms of athletic performance, with the goal of providing guidance to athletes and coaches in optimizing their nutritional strategies. The study conducted a systematic search of electronic databases (i.e., PubMed, Web of Science, Scopus) using keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 280 publications
0
3
0
Order By: Relevance
“…Consuming a snack or meal high in carbohydrates before exercise ensures optimal muscle glycogen reserves. On the other hand, low pre-exercise glycogen levels result in early fatigue, reduced training intensity, depleted muscle glycogen, impaired muscle contraction, glycogenolysis, and protein degradation ( 34 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consuming a snack or meal high in carbohydrates before exercise ensures optimal muscle glycogen reserves. On the other hand, low pre-exercise glycogen levels result in early fatigue, reduced training intensity, depleted muscle glycogen, impaired muscle contraction, glycogenolysis, and protein degradation ( 34 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, those who struggle to meet their micronutrient needs may benefit from supplementation, guided by a sports nutritionist ( 91 , 92 ). It’s crucial to emphasize that while micronutrients are crucial for health, they do not exert ergogenic effects, and factors like low-energy diets, vegetarianism, illness, and injuries can contribute to micronutrient deficiencies ( 40 , 93 ).…”
Section: Resultsmentioning
confidence: 99%
“…These interventions offer strategies for fueling, timing, and supplementation to support energy, recovery, and immune function. They also address essential element requirements, ensuring athletes receive vital micronutrients ( 82 ). Moreover, they consider individual variations in genetic profiles, metabolomics, nutrient utilization, and dietary preferences or restrictions ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a comprehensive systematic review of the literature in sports medicine emphasized the importance of micronutrients for athletes' health, physical performance, and mental well-being. It suggested that by ensuring adequate levels of micronutrients, athletes can give themselves a competitive edge and maximize the potential of their training (Ghazzawi et al, 2023). For example, higher intakes of vitamin B, particularly B7, have been linked to a lower incidence of depression in the general population (Mahdavifar et al, 2021).…”
Section: Journal Of Coaching and Sports Science | 67mentioning
confidence: 99%